Characterization of Senegalia senegal (L.) Britton gum planting in the Ouaddaï province, Chad - Ngaryo, Fidèle Tonalta; MBAYNGONE, Elisée; Ngarnouber, Chanceyambaye (Indian Journal of Agroforestry, 2025)
The study was carried out in a 25 hectare plantation set up in the Sahelian zone of Abougoudam in the Ouaddaï Province in Chad. The objective of the study was to determine the structure, fruiting and the correlation between the structure and fruiting of Senegalia senegal (L.) Britton. A sample of 101 individuals chosen at random from 253 in a demarcated plot of 4 hectares was monitored from May to September 2015. The experimental setup is a complete block made up of 5 simple linear transects, each 200 m long and 20 m wide, separated from each other by a gap of 20 m wide. The choice of experienced individuals was made randomly in the five transects. The results obtained showed that young plants are very poorly represented (3%) as are adult individuals (12%). However, individuals of average height (between 3 m and 7 m) are more represented (85%), thus demonstrating a shrubby structure of the plantation. The low proportion of young individuals and adult individuals explains low regeneration and intense anthropization. The arrangement according to the circumference and the diameter of the crown allows us to see that individuals from the middle classes are better represented than those from the large and small classes. The average distance separating individuals from each other is maximum (17.03 m), thus demonstrating a low density of the Senegalia senegal population per hectare. Fruiting is remarkable at stage Fr5 (98%) in May, low at stage Fr1 in June (2%) and average at stage Fr2 (38%) in June. In August and September, it is estimated at 79% and 91% at the Fr3 stage. There is a positive correlation between dendrometric parameters and stages Fr2 and Fr3.